(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Myths play a momentous role in human culture and civilization. As myths are the narratives through which humankind depict issues related to origin, creation, life, death, history, religion, social and economic traditions and culture, therefore, it is an inseparable part of human race. R. K. Narayan is a true painter of Indian life. His realistic approach makes his work have a universal appeal, touching the inner chord of the entire humankind. He uses myths in his work not as narratives of past but as the foundation of morality, virtue, righteousness in human life that brings it more close to reality. The paper “Myths as Narrative of reality in R. K. Narayan’s The Financial Expert” explores the work of Narayan in the light of his application of myths.